O que você faz com seu lixo? Estudo sobre a destinação do lixo na zona rural de Cruz Alta/RS- Passo dos Alemães - Pinheiro, Damaris Kirsch; Deboni, Lidiane (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2010)
Many environmental problems are occurring nowadays, and among them is the question of thedestiny of solid waste - the garbage. Its correct destination becomes increasingly important as theincorrectly packaging can harm the environment and the general population. In rural areas,garbage collection is often impractical. Therefore, the residents should make the final destinationby themselves. Seeking an environmental awareness through informal education, this study aimsto identify the destination that is given to household waste produced by families in Passo dosAlemães community,Cruz Alta rural area, and promote environmental awareness distributingflyers to local residents. For this, it was necessary to verify if the residents do some kind ofseparation of waste to determine whether the deposition techniques of waste in nature cansomehow affect the environment. The methodological approach was quantitative questionnaireswere conducted with local residents. The results show that the population, who lives in this community uses some different forms for garbage disposal in nature, the most common use isditches or holes in the ground made for the deposit of waste. A sector of residents deposited in adump off in Cruz Alta. The burning of garbage was also mentioned in the research, therebyproducing toxic gases in the environment .Only with the creation of new habits you can build asociety more committed to the environment. The research also highlights that since being theresidents responsible for the disposal of waste, it is necessary to understand that the respondentsshould improve their techniques of waste disposal in nature, but should take into account theirknowledge.